Identifikasi Minat dan Kemampuan Peserta Didik Menulis Teks Deskripsi dengan Menggunakan Media Objek Benda Kesayangan - Rahmawati, Rahmawati; Hasanah, Sri Uswatun; Yuniar, Yuniar (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to identify students' interest in writing descriptive texts using images of favorite objects. The informants were grade VII students of MTs Negeri 1 Palembang. The problems found were the low quality of students' descriptive writing, such as low ability to express ideas, unclear description of objects, text structure errors, limited word choice, and spelling and punctuation errors. The research method used qualitative descriptive and data collection techniques in the form of descriptive text writing assignments and interviews. The results showed that students' interest in writing descriptive texts was high. The aspects of title selection and the suitability of the text content were relatively good, but deficiencies were found in the use of vocabulary, sentence accuracy, and the application of spelling and writing. Factors found were lack of knowledge of word functions, minimal vocabulary, and students' lack of accuracy in writing. This study confirms that image media can help students generate ideas and increase interest in writing, although intensive learning regarding word choice and spelling is still needed. The implications of this research indicate the need for teachers to provide reinforcement of material regarding word usage, spelling, and provide more visual media-based writing exercises to improve students' literacy skills.